EM BUSCA DO ETHOS COMUNITÁRIO - UNIVERSIDADES CATARINENSES MANTIDAS POR FUNDAÇÕES PÚBLICAS DE DIREITO PRIVADO, UM OLHAR A PARTIR DO PLURALISMO JURÍDICO - Carlos Magno Spricigo Venerio (Universidade Federal de Santa Catarina, 2011)
The study intends to analyse the current situation in the universities from Santa Catarina‟s state that are maintened by public foundations under private law, from a comunnitary- participatory legal pluralism view and in the current perspective of the university management. In the turn of the century those institutions were confronted with a unprecedented scenario of paid universities‟ virtual monopoly end in their range, due to private universities expansion and the current increase of State‟s public investment in higher education, this institutions are looking for the empowerment of their Community organizational identity, with emphasis in the practice of democratic management‟s statement. From the enrollment‟s data in the last decade; meeting requiriments for accreditation in the way of universitary organization; and the analysis of provost‟s multiple systems of election, the study seeks to identify trends for paid higher education inserted into the ACAFE‟s - Associação Catarinense das Fundações Educacionais - system in procces of migration to the federal educational system.